Methylnitrosourea, dimethylbenzanthracene and benzoapyrene differentially affect redox pathways, apoptosis and immunity in zebrafish - ALTURFAN, EBRU IŞIK (SAGE PUBLICATIONS LTD, 2020)
Cancer continues to be a major cause of mortality globally. Zebrafish present suitable models for studying the mechanisms of genotoxic carcinogens. The aim of this study was to investigate the interaction between oxidant-antioxidant status, apoptosis and immunity in zebrafish that were exposed to three different genotoxic carcinogens methylnitrosourea, dimethylbenzanthracene, benzoapyrene and methylnitrosourea + dimethylbenzanthracene starting from early embryogenesis for 30 days. Lipid peroxidation, nitric oxide levels, superoxide dismutase and glutathione-S-transferase activities and mRNA levels of apoptosis genes p53, bax, casp3a, casp2 and immunity genes fas, tnf alpha and ifn gamma 1 were evaluated. The disruption of the oxidant-antioxidant balance accompanied by altered expressions of apoptotic and immunity related genes were observed in different levels according to the carcinogen applied. Noteworthy, ifn gamma expressions decreased in all carcinogen-exposed groups. Our results will provide basic data for further carcinogenesis research in zebrafish models.
Keywords: Methylnitrosourea; dimethylbenzanthracene; benzoapyrene; antioxidant; apoptosis; immunity; zebrafish; NITRIC-OXIDE SYNTHASE; METHYL-N-NITROSOUREA; OXIDATIVE STRESS; SUPEROXIDE-DISMUTASE; INTERFERON-GAMMA; IN-VIVO; CANCER; DMBA; EXPRESSION; EXPOSURE